Public Relations Management in Enhancing Parental and Community Participation: A Case Study at State Junior High School - Hafizotul Munawwaroh; Siti Raudhatul Jannah; Summiyani (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
This study analyzes public relations management in enhancing parental and community participation at State Junior High School 3 of Jambi City. The research employs a qualitative case study approach, collecting data through interviews, observations, and document analysis involving the principal, teachers, parents, the school committee, and community leaders. The findings indicate that public relations management is implemented systematically through three stages: planning, implementation, and evaluation. The planning stage includes coordination meetings and structured programs such as the annual meeting, social-religious activities, and the CARITI Program, supported by digital communication. Parental involvement, however, remains largely consultative. Program implementation effectively disseminates information and increases parental attendance, but active collaboration is still limited. Evaluation is conducted periodically using attendance and communication effectiveness indicators, yet parental participation in reflective and decision-making processes remains minimal. Overall, public relations management supports parental participation but remains consultative. Strengthening dialogue, participatory planning, and structured evaluation is necessary to foster a collaborative and sustainable partnership among the school, parents, and community leaders.